2020
DOI: 10.1371/journal.pone.0244157
|View full text |Cite
|
Sign up to set email alerts
|

A proteomics-based method for identifying antigens within immune complexes

Abstract: A novel approach to recover and identify immune complexes (ICs) was developed using size exclusion chromatography (SEC) and affinity chromatography on immunoglobulin binding columns (HiTrap Protein G). The purification process was monitored by 1D SDS-PAGE, protein staining, Western blotting and, finally, liquid chromatography tandem mass spectrometry (LC MS/MS) was used to identify the recovered antigens. This approach was applied to serum with artificially created immune complexes (ICs) comprising vaccine ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Its widespread offline utilization is due to the purification capacity of intact proteins with mild chromatographic conditions to permit further additional sample preparation steps with minimal impact on the conformational structure. The type of analytes and samples investigated by SEC in recent studies included exosomal proteins in human plasma [30], plasma exosomal proteins of corneal epithelial injury [31], extracellular vesicles in cancer cells [32,33], foam of recombinant biosurfactant apolipoprotein [34], peptides in alcalase hydrolisated pollen [35], circulating microparticles proteins to identify preterm babies before the end of 35 weeks of gestation [36], extracellular vesicle in cord blood of preterm and term births [37], α-Glucosidase-inhibitory peptides in dry-cured ham [38], extracellular vesicle in blood plasma [39], proteins in endogenous membrane proteins [40], N-Glycoproteins and phosphoproteins in human urine [41], high-density lipoproteins from plasma [42], proteins in antivenoms [43] and venoms of snakes [44], artificially created immune complexes on human serum [45], labelled proteins of E. coli lysate [46], extracellular vesicles in serum [47], β-Type Hemocyanin in shrimps [48], and extracellular vesicles in PLB-985 neutrophil-like cells [49].…”
Section: 1mentioning
confidence: 99%
See 3 more Smart Citations
“…Its widespread offline utilization is due to the purification capacity of intact proteins with mild chromatographic conditions to permit further additional sample preparation steps with minimal impact on the conformational structure. The type of analytes and samples investigated by SEC in recent studies included exosomal proteins in human plasma [30], plasma exosomal proteins of corneal epithelial injury [31], extracellular vesicles in cancer cells [32,33], foam of recombinant biosurfactant apolipoprotein [34], peptides in alcalase hydrolisated pollen [35], circulating microparticles proteins to identify preterm babies before the end of 35 weeks of gestation [36], extracellular vesicle in cord blood of preterm and term births [37], α-Glucosidase-inhibitory peptides in dry-cured ham [38], extracellular vesicle in blood plasma [39], proteins in endogenous membrane proteins [40], N-Glycoproteins and phosphoproteins in human urine [41], high-density lipoproteins from plasma [42], proteins in antivenoms [43] and venoms of snakes [44], artificially created immune complexes on human serum [45], labelled proteins of E. coli lysate [46], extracellular vesicles in serum [47], β-Type Hemocyanin in shrimps [48], and extracellular vesicles in PLB-985 neutrophil-like cells [49].…”
Section: 1mentioning
confidence: 99%
“…However, some works employ time-based separation on a conventional chromatographic run, when the adsorbent is packed on a column. One example of analyte purification performed on a chromatographic run is the purification of immunocomplexes artificially created by influenza vaccine spikes on human serum [102]. The first step of the workflow was an SEC prefractionation step that size-separated the immunocomplexes created between immunoglobulin and vaccine peptides.…”
Section: Offline Affinity Chromatography Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach is still relatively new and there is active development in the field to try to evaluate how best to identify complexes and control for error [23]. A recent report showed that SEC applied to serum could be used to enrich the high molecular weight (polymeric) fraction of immune complexes followed by purification with Protein G to purify the immune complexes [24]. In addition to using SEC for the identification and quantification of protein complexes and the enrichment of the high molecular weight fractions, studying the protein elution profile over the course of the chromatogram is valuable to help determine whether the protein is present as a single monomer eluting at its expected molecular weight, or whether the protein is present as a polymer or in a complex.…”
Section: 2mentioning
confidence: 99%